Geomorphologische Kartierung in der Apolobamba-Kordillere (Bolivien) Anwendung des Legendenkonzepts der GMK 100 in einem randtropischen Hochgebirge - Rafiqpoor, M. Daud (ERDKUNDE, 1994)
After an introductory discussion of the approach of geomorphologically detailed mapping (GMK), this paper proceeds to present the application of the recently developed German GMK legends concept at a scale of 1:100,000 (GMK 100) to the mapping of the high mountain range on the edge of the tropics (Apolobamba Cordillera, Bolivia). The paper addresses problems which arise in the application during fieldwork of this methodology. In general the legend of the GMK 100, supplemented by some additions to the landform ensemble of the periglacial phenomena in the sub-nival altitudinal belt of high mountains, proved to be a very qualified basis for geomorphological mapping even in the tropical mountain ranges at high altitudes. It was certainly possible to confirm this experience in the Bolivian field when applying the GMK approach of Central European high mountains in respect of foregoing the representation of slope gradient areas and vaulting lines in the GMK of high mountains. As a result of the geomorphological research undertaken in Bolivia, those spatial units which are characteristic for the area under investigation in respect of hypsometric landform development, geology, and hydrological conditions were described on the basis of the GMK 1 00 of the Charazani Uplands. The geomorphological altitudinal belts of the Apolobamba Cordillera are discussed in a scheme of the three-dimensional arrangement of the landform ensemble as an example for the asymmetric construction of the altitudinal limits in the high mountain areas of the Andes of the marginal tropics. Checking the terrain and providing supplements for a geological map of the Bolivian Geological Service (GEOBOL), which had been based predominantly on photo geological interpretations, also permitted the making of a geological map at a scale of 1:100,000 of the area under investigation to be revised as a basis for the detailed geomorphological map. This paper concludes with a brief sketch of the geomorphologically relevant geological-petrographic conditions in the study area, which acts as a description of the accompanying geological map (Supplement VII).